Racial Disparities in Extremity Soft-Tissue Sarcoma Outcomes: A Nationwide Analysis. (December 2015) - Alamanda, Vignesh K.; Song, Yanna; Schwartz, Herbert S.; Holt, Ginger E.
Abstract : Background: Racial disparities in access and survival have been reported in a variety of cancers. These issues, however, have yet to be explored in detail in patients with soft-tissue sarcomas (STS). The purpose of this paper was to investigate the independent role of race with respect to survival outcomes in STS. Methods: A total of 7601 patients were evaluated in this study. A SEER registry query for patients over 20 years old with extremity STS diagnosed between 2004 and 2009 (n=7225) was performed. Survival outcomes were analyzed after patients were stratified by race. Multivariable survival models were used to identify independent predictors of sarcoma-specific death. The Wilcoxon rank-sum test was used to compare continuous variables. Statistical significance was maintained at P <0.05. Results: This study showed that African American patients were more likely to die of their STS. They were younger at presentation ( P =0.001), had larger tumors ( P <0.001), had less surgery ( P =0.002), received radiotherapy less frequently ( P =0.024), had higher family income ( P <0.001), and were less likely to be married ( P <0.001). African American race by itself was not an independent predictor of death. Conclusions: African Americans encounter death due to STS at a much larger proportion and faster rate than their respective white counterparts. African Americans frequently present with a larger size tumor, do not undergo surgical resection, or receive radiation therapy as frequently as compared with their white peers. Barriers to timely and appropriate care should be further investigated in this group of at-risk patients.